2019
DOI: 10.3389/fimmu.2019.01413
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma-Associated Paraneoplastic Autoimmune Multiorgan Syndrome—From Pemphigus to Lichenoid Dermatitis

Abstract: Introduction: Paraneoplastic autoimmune multi-organ syndrome (PAMS) is a rare clinical condition characterized by variable and heterogeneous clinical phenotypes in the presence of neoplasias which largely depend on the activation of humoral and cellular immune responses. Clinically, these patients present with a spectrum of antibody-driven pemphigus-like lesions to graft-vs.-host-disease-like exanthemas with a lichenoid inflammatory infiltrate in the skin. PAMS is occasionally associated with thymom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 41 publications
2
31
0
8
Order By: Relevance
“…PNP is an obligate PD usually associated with B-cell lymphomas and hematological malignancies [7]. In 2001, Nguyen et al suggested the term "paraneoplastic autoimmune multiorgan syndrome" (PAMS) as several organs are affected and autoantibodies bind several tissues [8,9]. PNP usually affects patients aged between 45 and 70 years [7,10,11].…”
Section: Paraneoplastic Pemphigus (Pnp)mentioning
confidence: 99%
See 2 more Smart Citations
“…PNP is an obligate PD usually associated with B-cell lymphomas and hematological malignancies [7]. In 2001, Nguyen et al suggested the term "paraneoplastic autoimmune multiorgan syndrome" (PAMS) as several organs are affected and autoantibodies bind several tissues [8,9]. PNP usually affects patients aged between 45 and 70 years [7,10,11].…”
Section: Paraneoplastic Pemphigus (Pnp)mentioning
confidence: 99%
“…Nearly 84% of all PNP are found in association with hematologic neoplasms or disorders. Among these, non-Hodgkin's lymphoma, chronic lymphocytic leukemia, Castleman's disease, and thymoma are mostly reported, accounting respectively for 38.6%, 18.4%, 18.4%, and 5.5% of all PNP cases [7,9,11]. Usually, the neoplasm is detected before the onset of PNP, but in about 30% of cases, the skin manifestations lead to the detection of an occult neoplasia [7,11].…”
Section: Paraneoplastic Pemphigus (Pnp)mentioning
confidence: 99%
See 1 more Smart Citation
“…5). Besides acantholysis, PNP shows a lichenoid lymphocytic infiltrate along the dermal-epidermal junction by histopathology [136,137]. Serologically, PNP is only rarely associated with IgG antibodies against desmoglein 3 and desmoglein 1, which are the main antigenic targets of pemphigus vulgaris and foliaceus respectively, whereas IgG autoantibodies against envoplakin, periplakin and the protease inhibitor, alpha-2-macroglobulin-like antigen-1 are more frequently detected.…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%
“…Based on the evidence of increased levels of IL-6 in PNP sera and the crucial role of IL-6 in Castleman's disease [157,158], tocilizumab, a monoclonal antibody targeting IL-6, has been successfully applied as a treatment for PNP in this context, but seems to have limited effect in preventing bronchiolitis obliterans [159,160]. Rituximab, with or without chemotherapy, represents an effective therapeutic option for PNP [146,161]; thymoma-associated PNP or multi-organ syndrome also respond well to rituximab treatment, but a significant proportion of these patients still die as a result of infections and sepsis [137].…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%